The Necessity of the Digital Single Market Strategy for Small Media Markets: Case of the Biggest Video-on-Demand Platforms in Lithuania and Estonia - Dabrovolskas, Audrius (Žurnalistikos tyrimai, 2018)
[full article and abstract in English]This article analyzes the biggest Lithuanian and Estonian video-on-demand (VOD) platforms including Telia, their capabilities for fostering European film production and mass media in general. It is important to accentuate that non-linear TV and VOD services are attracting more and more users in Europe, and it is even considered that VOD could become a strong competitor for theatrical releases in film distribution, while, in the context of mass media, the growth of users might be associated with potential threats of propaganda, which still has its own distribution mechanisms within linear TV. However, the audiovisual content that is being supplied for the users of VOD platforms and TV is also regulated by the Audiovisual Media Service Directive (AVMSD). Without regulation, the users of VOD platforms and TV might face a limited choice of audiovisual content. Therefore, the Digital Single Market (DSM) strategy is aimed at creating a single market in Europe and eliminating the geo-blocking that limits user abilities to use VOD services during travel across borders while also establishing better access to digital goods and services at the same time. Looking from the perspective of the VOD platform, a DSM strategy might bring about a monopolization of VOD services in Europe; in that case, the little markets of the Baltic States would suffer. Another important issue that small media markets come across is related to the level of propaganda that is being transmitted from Russian TV channels that are registered in different EU countries. The article argues, and the research results show, that a DSM strategy and the elimination of geo-blocking do not eliminate the problem of fostering European audiovisual content that is and could be available to the users of VOD platforms in Lithuania and Estonia, and that these measures do not pay significant attention to EU’s consumer protection issues.
Keywords: Digital Single Market, film distribution, VOD, Audiovisual Media Service Directive, propaganda.